Antimicrobial resistance in agricultural environments in Brazil – A concern from a One Health perspective - Paula Fernanda Alves Ferreira; Danielli Monsores Bertholoto; Juliana Ferreira Nunes; Gustavo Souza Lima Sant’Anna; Thereza Cristina da Costa Patricio; Júlia Ferreira Xavier; Hosana Dau Ferreira de Souza; Shana de Mattos de Oliveira Coelho; Miliane Moreira Soares de Souza; Irene da Silva Coelho (Revista Brasileira de Ciência do Solo)
ABSTRACT Antimicrobial resistance is a global public health concern that requires an integrated approach including human, animal and environmental health. Agricultural environments, such as soil, animal waste and irrigation water, play crucial roles in the dynamics of antimicrobial resistance, as they act as reservoirs and pathways for disseminating resistance determinants. However, these agricultural environments are still often underestimated or neglected in many studies. This study aimed to address antimicrobial resistance in agricultural environments in Brazil and summarize the current state of knowledge about this issue in the country. Google Scholar, Google, ISI Web of Knowledge and Web of Science databases were searched for Portuguese, English and Spanish articles addressing antimicrobial resistance in agricultural environments in Brazil published through 2023. Different terms were used, and the findings were categorized according to the research questions posed. A total of 36 articles were found, 20 of which focused on antimicrobial resistance in animal waste from livestock production, 13 addressed antimicrobial resistance in agricultural soils, two considered both environments, and only one considered antimicrobial resistance associated with irrigation water in different agricultural environments. In all studies, diverse classes of resistant bacteria and antimicrobial resistance genes and mobile genetic elements were detected. However, the number of articles addressing this topic in Brazilian agricultural environments - in animal waste, followed by soils and, to a lesser degree, irrigation water - is still quite limited, revealing significant gaps to be filled. Therefore, it is essential to conduct more studies on antimicrobial resistance in these environments to elucidate their roles as reservoirs and sources of antimicrobial resistance and assess the risks to public health.